Synthesis and properties of epoxy-phenolic clay nanocomposites (eXPRESS Polymer Letters)
An epoxy-phenolic resin suitable for use as a composite matrix was reinforced with modified nanoclay (montmorillonite type). Characterization by x-ray diffraction and transmission electron microscopy (TEM) demonstrated that intercalated nanocomposites were formed with an inter-gallery distance of approximately 10 nm. The influence of nanoparticles on tensile strength and modulus, fracture toughness, and impact toughness was measured and compared with the unreinforced polymer. The results revealed that the maximum enhancement in stiffness and toughness was achieved with 2.5 wt% filler content. The enhancement in toughness behavior was attributed to the activation of multiple energy-dissipating damage mechanisms in the nanocomposites.